Lasykar Syiah Hudan Constribution in Business Distribution of Islam in XIII Masehi Century Aceh - Usman Ibrahim; Bachtiar Akob; Imam Hadi Sutrisno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Lasykar Syiah Hudan is part of the Zawiyah Cot Kala College, the oldest in Aceh and Southeast Asia, built in the era of the sixth Sultan Peureulak Muhammad Amin Syah Johan Sovereign,early X century AD. One of the great scholars / teachers is Chik Abdullah Kan'an. Center for training activities in Aramiyah / Bayeun (present-day East Aceh). Besides being a professor, Chik Abdullah Kan'an was an adult who was also the leader of Wazirul Harb, the Shia Hudan army in Bandar Khalifah, known as "Teungku Chik Syiah Hudan" and his deputy was Commander Meurah Johan. The realization of the Lasykar Syiah Hudan, have contributed a lot (donations) in the effort to spread Islam through the missionaries / soldiers of Lasykar Syiah Hudan in Aceh and Nusantara / Southeast Asia inXIII AD. For example Meurah Gajah to Tamiang, Meurah Khair to Cot Girek Lhoksukon, Meurah Giri to Seureuleue Aceh Tengah.The objectives of this study were (1) to trace the location of the Syiah Hudan army, (2) the guidance and training of the Syiah Hudan Zawiyah Cot Kala army, and (3) the efforts and contribution of the Syiah Hudan army in the expansion and development of Islam in Aceh.This research design uses historical and critical methodologies. According to Gottschalk (1975: 18), that the study of the critical historical method, its substance excludes inauthentic material and concludes reliable testimony about the original material. The critical historical method consists of 4 (four) steps of the research process, namely gathering sources (heuristics), including primary, secondary and tertiary sources; criticizing these sources (both internal criticism and external criticism), interpreting the facts obtained from criticizing these sources, and historiography, namely reconstructing existing facts that have been interpreted in the form of historical writing, namely the process of synthesizing facts critically. The results of his research show that the contribution of members of the Shia Hudan missionary army, part of Zawiyah Cot Kala, succeeded in introducing Islamic da'wah in Aceh.